Inviolability of dignity (Journal of actual problems of jurisprudence, 2019)
Person, provided the legal system of constitutional guarantees , which include guarantees of the right to a dignified andsecure life , can fully develop , operate and function in the system of social relations . In Kazakhstan, the interests ofindividuals are regulated by sectoral system of domestic law and a certain level of integrity. Rights and freedoms ofman and citizen occupy one of the first sections of the Basic Law and establishes priorities of the entire state systemof the country . However , the inviolability of dignity as we are not talking about self-sufficient category , its trulydemocratic nature requires constant scientific, practical and dialectical development , taking into account all developingsocial relations , the role and status of the individual values .Key words: dignity, inviolability of dignity, identity, torture.